Respon Biologis Pemberian Bungkil Kelapa Hasil Fermentasi dengan Trichoderma harzianum dalam Ransum Terhadap Performans Ayam Pedaging - Mairizal, Mairizal; Erwan, Edi (Fakultas Peternakan Universitas Jambi, 2008)
The experiment was aimed to see the effect of coconut cake fermentation with Trichoderma Harzianum (TH) in ration on the performance of male broiler. 100 heads of three-day-old broiler chiken were arranged to completely randomized treatment with 5 kinds of ration such as 0%, 5%, 10%, 15% and 20 % of coconut cake fermentation with TH and 4 times replication. Data collected were feed consuption, body weight gain and feed conversion. Analisys of variance and Duncan’s multiple range test were used to analize the data. The result showed that the use of coconat cake fermentation with TH significantly (P<0,05) reduced body weight gain, but there was no effect (P>0,05) on feed consumption and feed conversion. From the experiment result we concluded that only 15 % of coconut cake fermentation with TH which can be suggested in male broiler chiken ration